Factors that affect employees’ behaviour among the non executive workers in Nitar’s Palm Oil Industries / Nurul Syafriena Khairudin - Khairudin, Nurul Syafriena (2010)
Employees‘ behaviour plays an important role in determining the successfulness of an organization. Organizations around the world face similar business challenges such as the difficulty to manage the employee especially the non executive workers. If the employees are well-behaved, the level of self-esteem and motivation will be high and therefore, it will influence the organization‘s performance resulting in higher productivity and simultaneously bring onto organizational successfulness. When looking at this problem area, we found that there may be actions that companies can use to cater to this problem in reducing the employee‘s deviant behaviour. The past researcher shows that there are many factors that affect the employee‘s behaviour. This study focus on three factors that could affect employee‘s behaviour which is organization‘s culture, structure and system and management practices. This study has been conducted within Nitar‘s Palm Oil Industries and it involved respondents among non executive workers. For measuring the three factors, quantitative method has been selected, using questionnaire that were determined through Likert Scale. Results of the present study showed that the most influential factors that affects employee‘s behaviour among non executive level in Nitar‘s Palm Oil Industries is organization‘s culture. It also shows that organization‘s culture has a positive correlation relationship with employee‘s behaviour in Nitar‘s Palm Oil Industires. Several recommendations were given such as instilling good culture within the organizations through great examples and leadership. Besides that, clear cut explanations and company‘s support towards employees may play a big role in increasing the performance level of the company.